Sequential treatment of anti-PD-L1 therapy prior to anti-VEGFR2 therapy contributes to more significant clinical benefits in non-small cell lung cancer - Qiao-xin Lin; Wen-wen Song; Wen-xia Xie; Yi-ting Deng; Yan-na Gong; Yi-ru Liu; Yi Tian; Wen-ya Zhao; Ling Tian; Dian-na Gu (Neoplasia: An International Journal for Oncology Research)
Objective: Anti-angiogenic therapy and immune checkpoint blockade therapy are currently important treatments for non-small cell lung cancer. However, the combined use of the two therapies is controversial, and few studies have investigated the effects of different time sequences of the two therapies on treatment outcomes. Methods: The tumor-bearing mouse model was established and the mice were divided into four groups, including AA-ICB sequence group, ICB-AA sequence group, synchronization group and the control group. Immunohistochemistry was used to assess tumor microvessels and PD-L1 expression. Selected immune cell populations were evaluated using flow cytometry. Meta-analysis and clinical information were used to elucidate the clinical effects of administration sequence. Results: We found that anti-PD-L1 treatment followed by anti-VEGFR2 therapy exerts the best inhibitory effect on tumor growth. Different sequences of anti-angiogenic therapy and immune checkpoint blockade therapy resulted in different proportions of tumor microvessels and immune cell populations in the tumor microenvironment. We further revealed that the administration of anti-PD-L1 before anti-VEGFR brought more normalized tumor blood vessels and CD8+T cell infiltration and reduced immunosuppressive cells in the tumor microenvironment. Subsequent re-transplantation experiments confirmed the long-term benefits of this treatment strategy. The meta-analysis reinforced that immunotherapy prior to anti-angiogenic therapy or combination therapy have better therapeutic effects in advanced non-small cell lung cancer. Conclusion: Our study demonstrated that the therapeutic effect of anti-angiogenic treatment after immune checkpoint therapy was superior to that of concurrent therapy, whereas anti-angiogenic therapy followed by immunotherapy did not bring more significant clinical benefits than independent monotherapy.